Analisis Pengaruh Motivasi Intrinsik dan Ekstrinsik terhadap Kepuasan Kerja Karyawan Generasi Milenial - Ihda Nor; Teti Safari; Heri Usodo; Nyoman Sri Padmini; Wahyudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of intrinsic and extrinsic motivation on job satisfaction of millennial generation employees. Millennials have unique characteristics that influence the way they interpret their work. With a quantitative approach, data were collected through a survey of 150 millennial employee respondents from various industrial sectors. The results of multiple regression analysis show that both intrinsic and extrinsic motivation have a significant effect on job satisfaction, with intrinsic motivation having a more dominant influence. The implications of these results indicate the importance of organizations to adjust HR management strategies to the characteristics of the millennial generation.